Traditional Game Lato-Lato: Physics Learning Media to Improve Students’ Conceptual Mastery of Collision and Momentum Materials - Rafi Zidni; M K Mudzaki; Bayu Setiaji (Universitas Sebelas Maret, 2024)
Physics is a science that studies natural phenomena, but students' interest in this subject is often low because it is considered abstract and difficult. The traditional approach to physics learning, which often focuses on theory, is less appealing to many students. One effective way to increase students' understanding and interest is through experimentation and the use of adequate teaching aids. In this context, the traditional game of Lato-Lato shows great potential as an innovative learning medium. This research aims to find out the concept of physics through the lato-lato game. This article reviews Lato-Lato's role in teaching physics concepts, especially in collision and momentum matter. This study uses a literature review method to evaluate the existing literature related to the use of Lato-Lato in physics education. The review process involves identifying, selecting, and critically evaluating literature from various academic databases. The results of the study indicate that Lato-Lato can be an effective learning tool by integrating physics theory with real practice in an interactive and fun way. This game not only helps students understand difficult physics concepts through hands-on experience, but also increases their motivation and interest in learning physics. The integration of Lato-Lato in physics learning can enrich teaching methods by providing a more contextual and practical approach.